Q-Switched Laser for the treatment of mucocutaneous pigmentation on Peutz-Jeghers Syndrome - Abdo Salomão; Constança Pithon Pereira; Rodrigo Cesar Davanco; Daniella Grande Curi; Domingos Jordão (Sociedade Brasileira de Dermatologia (SBD), 2022)
Peutz-Jeghers syndrome (PJS) is a rare, autosomal dominant disease where there is a mutation in the tumor suppressor gene, with a greater predisposition to neoplasms, especially of the gastrointestinal tract. The first manifestations begin during childhood with the presence of mucocutaneous melanosis and, later, gastrointestinal hamartomatous polyps. We describe a case of a young woman whose initial PJS manifestation started during her childhood with cutaneous melanosis. Three sessions with the Q-switched 1064nm Nd:YAG and 532nm KTP lasers were performed to treat the melanosis with excellent results and without recurrence.